(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2020)
AlـSi alloys with compositions (0, 0.1, 0.5, 0.9 and 1.3 wt.% Si) were manufactured by chill block melt spinning method. The resulting ribbons samples have been characterized by xـray diffraction (XRD) and scanning electron microscope (SEM). Detailed analysis of (XRD) shows that presence of f.c.c Al solid solution and Si particles embedded within the aluminum grains. Microstructural examination resulted that microstructure of the melt spun ribbons are more fine and uniformly distributed. Rapid solidification technology led to increase the solubility of Si in αـAl as confirmed by XRD. Micro hardness measurements were also carried out by Vickers microـhardness tester at applied load 25gm forced and different dwell time. It is concluded that the Vickers hardness values are sensitive to applied load and indentation time. It is also found that the highest values of Hv is sensitive to presence of Si as columnar shape with fine grained of Al by high cooling rate.